If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -1) + 3 = 2x + -7 Reorder the terms: 2(-1 + x) + 3 = 2x + -7 (-1 * 2 + x * 2) + 3 = 2x + -7 (-2 + 2x) + 3 = 2x + -7 Reorder the terms: -2 + 3 + 2x = 2x + -7 Combine like terms: -2 + 3 = 1 1 + 2x = 2x + -7 Reorder the terms: 1 + 2x = -7 + 2x Add '-2x' to each side of the equation. 1 + 2x + -2x = -7 + 2x + -2x Combine like terms: 2x + -2x = 0 1 + 0 = -7 + 2x + -2x 1 = -7 + 2x + -2x Combine like terms: 2x + -2x = 0 1 = -7 + 0 1 = -7 Solving 1 = -7 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 3(2+X)=32 | | 4x^6+36x^5+80x^4=0 | | 21j-16j+3=18 | | -9x-4y=17 | | 9(3x-9)-7-2x=x | | 4=3x+31 | | 7(2x+9)+6=14x+69 | | X=7-2t*t | | 10x-12y=14 | | ln(5x+3)=0 | | 9x+2=7x+12 | | 2t^5-14t^4+20t^3=0 | | 3.5+2.5y=2y-3 | | x^4-29x^2+100= | | 2.333333333+3.333333333y=3y-4 | | 3+3y=y | | -1/2(2)+3/2=x | | 5+2j=3 | | x^6-19x^5-20x^4=0 | | 9x-63=7x+63 | | log(x)+log(x-2)=log(14) | | p(a)=a^2-2a-13 | | 16-1.5x=2+1.25x | | (-a-7b+4)5ab= | | 5x-15=3x+75 | | 10(200+X)=900 | | 4*-4.3*-2= | | 5x-15=3x+3 | | 16+12t+2t^2=0 | | 3v-6-5v=-2v-4 | | 5(w-3)=9w-23 | | 4u+4+u=3u-6+2 |